P236 Symptoms of anxiety and depression in inflammatory bowel disease. (16th January 2018) - Silva, J C; Silva, A P; Rodrigues, A; Rodrigues, J; Sousa, M; Machado, A S; Carvalho, J
Abstract: Background: Treatment of Crohn's disease (CD) and ulcerative colitis (UC) is usually directed at organic aspects of the disease, often disregarding psychosocial factors. A comprehensive strategy including identification of anxiety and depression are possible therapeutic targets to increase quality of life in inflammatory bowel disease (IBD). The present study aims to test the association between anxious and depressive symptoms with IBD activity and course. Methods: Of 221 patients followed in outpatient setting in October and November of 2017, 64 patients with confirmed IBD who accepted to participate in the study were selected. Patients with known mental illness followed by Psychiatry were excluded. Anxiety symptoms were quantified by Spielberg's Anxious State Inventory (STAI) and symptoms of depression by the Beck II Depression Scale (BDI-II). Results: Sixty-four patients were included, of which 75% with CD and 25% with UC. The mean age was 40 ± 13.99 years and 53.1% were female. Clinical remission rate was 87.5% in CU and 75% in CD, with an endoscopic remission rate of 25% in CU and 50% in CD. The correlation between anxiety and depression symptoms was significant (p <0.001, r = 0.73). There was no statistically significant difference in anxiety and depression scores between patients with CD and CU. The correlation of number of disease flairs with STAI and BDI-II scores was significant (STAI p = 0.023; BDI-II p = 0.017). In IBD patients, there was also a statistically significant association between STAI score (anxiety) and clinical remission, endoscopic remission and need for therapy step-up (p <0.05). In CD patients there was a significant association between anxiety and the presence of perianal disease ( p = 0.035). In UC patients, there was a significant association between anxiety and recent flair ( p = 0.021), use of emergency room ( p = 0.029), hospitalisation ( p = 0.029) and therapy step-up ( p = 0.013). In this group of patients a significant association between depressive symptoms and immunosuppressant or anti-TNF therapy was seen ( p = 0.009). Conclusions: In the analysed patients there was an association of anxious and/or depressive symptoms with frequency of disease flairs and disease activity. Screening for anxious and depressive symptoms may have a significant impact on the quality of life of patients with IBD.